Arthroscopic Removal of the Polyethylene Glenoid Component After Total Shoulder Arthroplasty: A Systematic Review. (December 2022) - Ozdag, Yagiz; Baylor, Jessica; Hayes, Daniel; Grandizio, Louis C
Purpose: To identify prior studies of arthroscopic glenoid component removal after total shoulder arthroplasty (TSA) and understand indications, techniques and patient outcomes. Methods: A search of the English language literature on arthroscopic removal of the glenoid component (ARGC) after TSA published between 2005 and 2021 was performed from MEDLINE and EMBASE databases. Articles with ARGC after TSA were identified and we recorded article characteristics as well as patient demographics and outcomes contained within the studies. Results: A total of six publications (two case reports and four retrospective case series) detailing the outcome of ARGC performed on twenty-five shoulders were identified. The average time from index procedure to glenoid removal was 117 months and mean age at time of ARGC was 75 years. Although patient reported outcomes measures (PROMs) varied in type and reporting style, all articles reported improvements in PROMs. Twenty patients in this systematic review were evaluated for post-operative complications and the complication rate was found to be 15% (n = 3). There were 2 cases (18%) of superior migration of the humeral head relative to the glenoid and no reported cases of anterior or posterior humeral head subluxation. Two of 25 patients (8%) underwent subsequent open revision procedures. Conclusions: The limited number of publications in this systematic review demonstrates that ARGC after TSA can result in improvements in both pain and PROMs. This less-invasive arthroscopic technique may be an alternative to open revision for lower demand patients; however, future prospective, comparative studies are necessary to better define indications.